2003
DOI: 10.1080/1475636031000152277
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of l-Canavanine Cytotoxicity: Arginyl tRNA Synthetase as a Novel Target for Anticancer Drug Discovery

Abstract: There is a clear need for agents with novel mechanisms of action to provide new therapeutic approaches for the treatment of pancreatic cancer. Owing to its structural similarity to L-arginine, L-canavanine, the beta-oxa-analog of L-arginine, is a substrate for arginyl tRNA synthetase and is incorporated into nascent proteins in place of L-arginine. Although L-arginine and L-canavanine are structurally similar, the oxyguanidino group of L-canavanine is significantly less basic than the guanidino group of L-argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 67 publications
1
41
0
Order By: Relevance
“…In canavanine (5) substituted oxygen atom due to its electron withdrawing nature destabilizes positive charge on the side chain guanidino group, resulting in $41 kJ mol À1 decrease in PA, comparing to arginine. This finding is consistent with results showing that structurally aberrant proteins (containing canavanine instead of arginine) do not function properly [31]. Obtained PA SC of canavanine (5) (5) could be underestimated [25].…”
Section: Arginine Homologues and Oxy-analoguessupporting
confidence: 82%
“…In canavanine (5) substituted oxygen atom due to its electron withdrawing nature destabilizes positive charge on the side chain guanidino group, resulting in $41 kJ mol À1 decrease in PA, comparing to arginine. This finding is consistent with results showing that structurally aberrant proteins (containing canavanine instead of arginine) do not function properly [31]. Obtained PA SC of canavanine (5) (5) could be underestimated [25].…”
Section: Arginine Homologues and Oxy-analoguessupporting
confidence: 82%
“…It is incorporated into nascent proteins in place of L-arginine. The oxyguanidino group of L-canavanine is significantly less basic than the guanidino group of arginine; as a result, L-canavanine-containing proteins are unable to form crucial ionic interactions, resulting in altered protein structure and function that could lead to cell death (2). Interestingly, L-canavanine inhibits violacein production in C. violaceum without interfering with growth.…”
Section: Discussionmentioning
confidence: 99%
“…Handelsman and her group showed that canavanine exuded from alfalfa seeds has the potential to affect the population biology of Bacillus cereus (31). L-Canavanine is incorporated in place of L-arginine into nascent protein chains during synthesis, resulting in altered protein structure and function and eventually leading to death of the targeted cell (7,119). In our recent work, we identified L-canavanine as a QSI compound and showed that the QSI activity is independent of its effect on bacterial growth (Table 2) (54).…”
Section: L-canavanine As a Quorum-sensing Inhibitormentioning
confidence: 99%